How Can Companies Give Voice and Support Family Transitions That Risk Being Invisible and Silent? - Bosoni, Maria Letizia; Mazzucchelli, Sara (Italian Sociological Review, 2023)
In the contemporary social context, family transitions become increasingly challenging and affect not only the family life but also the whole social context. With the term “transition” we mean periods of crisis, resulting from an event that modifies in a very significant way personal and family life and requires a process of redefinition so that a new equilibrium can be found. Such transitions are often invisible, but inevitably impact on family and professional life. This topic was dealt within a broader mixed-method research project “Ageless Talents - An observatory on the condition of over 50 employed women and men” funded by Valore D (https://valored.it/), in Italy aimed at understanding personal and family transitions in the life of over 50 workers, in particular deepening personal experiences and motivations. By focus group methodology specific understanding of managing illness in the workplace has been done and it will be presented in this contribution. The participants gave a decisive contribution by putting themselves at stake, sharing their personal experience in an atmosphere of listening, interest, mutual respect, and gratitude for the possibility of being called to tell their experience. This fact immediately gave us back the urgency and importance of giving voice and a space of speech to topics that usually struggle to find a suitable time, space, and interlocutor.